Oseltamivir in pregnancy and birth outcomes - Vera Ehrenstein; Nickolaj Risbo Kristensen; Brigitta Ursula Monz; Barry Clinch; Andy Kenwright; Henrik Toft Sørensen (BMC Infectious Diseases, 2018)
Abstract Background Prenatal exposure to influenza or fever is associated with risk of congenital malformations. Oseltamivir is used to treat influenza and to provide post-exposure prophylaxis. We examined the association between oseltamivir use during pregnancy and birth outcomes. Methods This was a nationwide registry-based prevalence study with individual level data linkage, in a setting of universal health care access. We included all recorded pregnancies in Denmark in 2002–2013, and used data from population registries to examine associations between dispensings for oseltamivir during pregnancy (first trimester, second/third trimester, none) and congenital malformations, foetal death, preterm birth, foetal growth, and low 5-min Apgar score. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were computed using propensity score matching. Results The study included 946,176 pregnancies. Of these, 449 had first-trimester exposure and 1449 had second/third-trimester exposure to oseltamivir. Adjusted ORs following first-trimester exposure were 0.94 (95% CI 0.49 to 1.83) for any major congenital malformation and 1.75 (95% CI 0.51 to 5.98) for congenital heart defects, based on 7 exposed cases. The association with congenital heart defects was present for etiologically implausible exposure periods and for known safe exposures. There was no evidence of an association between prenatal exposure to oseltamivir and any of the other birth outcomes assessed. Conclusions The study does not provide evidence of risk associated with oseltamivir treatment additional to that associated with influenza infection.